2018
DOI: 10.1149/2.0271801jss
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Light Extraction from Luminescent Materials

Abstract: Light extraction from luminescent materials, where luminescence generated in a high refractive index medium must be coupled to a lower index medium, is a complex problem with significant ramifications for efficient LED and phosphor converted LED lighting. We derive thermodynamic arguments which show that light transmission for incident Lambertian light through arbitrary structured or non-structured surfaces is always limited by the ratio of incident to output étendues. Numerical simulations of various strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…Even if WLEDs-based display and lighting devices exhibit good photometric parameters, their performances in terms of external quantum efficiency and service life can be further impro ved [2][3][4]. This latter could be lengthened thanks to a better thermal dissipation whereas the former relies on both Internal Quantum Efficiency (IQE) and Light-Extraction Efficiency (LEE), which represents the ratio between the number of photons extracted to the air and the number of photons generated in the active layer [2,4,5]. Actually, the emitted light is hard to extract into the air since there is a gap between the high refractive index of the phosphor (n1.8 for the most common used Y3Al5O12:Ce 3+ ̶ YAG:Ce phosphor) and the air (n1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if WLEDs-based display and lighting devices exhibit good photometric parameters, their performances in terms of external quantum efficiency and service life can be further impro ved [2][3][4]. This latter could be lengthened thanks to a better thermal dissipation whereas the former relies on both Internal Quantum Efficiency (IQE) and Light-Extraction Efficiency (LEE), which represents the ratio between the number of photons extracted to the air and the number of photons generated in the active layer [2,4,5]. Actually, the emitted light is hard to extract into the air since there is a gap between the high refractive index of the phosphor (n1.8 for the most common used Y3Al5O12:Ce 3+ ̶ YAG:Ce phosphor) and the air (n1).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the emitted light is hard to extract into the air since there is a gap between the high refractive index of the phosphor (n1.8 for the most common used Y3Al5O12:Ce 3+ ̶ YAG:Ce phosphor) and the air (n1). Then, the device suffers from a loss of light because a large fraction of the produced photons are backscattered to the chip or trapped in dielectric structures inherent to the substrate (luminescent coatings) due to Total I nternal Reflection (TIR) and the presence of a waveguide mode [5][6][7]. Several approaches have been reported to boost LEE value.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that: i) strong backscattering occurs in HSYAGs samples, and the degree of backscattering increases with the porosity; ii) the side emission ratio remarkably decreases with increasing porosity; and iii) the top emission ratio could reach >95% in all HSYAGs samples. So, the high light scattering contributes to the strong backscattering, which is mainly ascribed to the small scattering length . This means the light emission is somehow engineered to be directional, namely, the backward direction, which is very favored in the reflection mode.…”
Section: Resultsmentioning
confidence: 99%
“…So, the high light scattering contributes to the strong backscattering, which is mainly ascribed to the small scattering length. [54][55][56] This means the light emission is somehow engineered to be directional, namely, the backward direction, which is very favored in the reflection mode. Since strong backscattering also hinders the light propagation in the lateral direction and confines the light emission close to the surface, the side emission ratio due to the TIR is greatly decreased.…”
Section: Microstructures and Optical Properties Of The Yag:ce Ceramicsmentioning
confidence: 99%
“…In the case of solid-state lighting, the emitted light is hard to extract into air because there is a gap between the high refractive index of the phosphor (around 1.8 for the most common used Y 3 Al 5 O 12 :Ce 3+ (YAG:Ce) phosphor) and the air ( n = 1). This kind of device usually suffers from a loss of light because a large fraction (typically at least 80% , ) of the produced photons are backscattered to the chip or trapped in dielectric structures due to total internal reflection (TIR), under the form of guided modes. ,, Light, in that case, can eventually escape through the edges. Allowing these guided modes to be extracted can thus significantly enhance the LEE and ultimately the EQE.…”
Section: Introductionmentioning
confidence: 99%